PEMBAHARUAN HUKUM INDONESIA SEBAGAI PERLINDUNGAN BAGI INVESTOR DI TENGAH FENOMENA INVESTASI BODONG - Bloude, Bastian; Ratnawati, Elfrida (Ensiklopedia of Journal, 2024)
The proliferation of fraudulent investments causing substantial losses to the general public in Indonesia has prompted the Indonesian government to take action through legislative and central government bodies to enact Law Number 4 of 2023 on the Development and Strengthening of the Financial Sector. This legislation aims to address the need for legal reform in certain provisions of the financial sector that are considered outdated and no longer accommodating current technological advancements and investment practices in Indonesia, particularly in the trading of cryptocurrencies as commodities. The establishment of this law also serves as a response to safeguard investors engaging in investment practices or capital investment in Indonesia. In executing this research, the primary objective is to determine whether the legal reforms undertaken by the Indonesian government can provide legal protection to investors in Indonesia amid the fraudulent investment phenomenon. This study is conducted through a normative research approach with a descriptive methodology to illustrate how Law Number 4 of 2023 can offer legal protection to investors in Indonesia. The research relies on secondary data sources obtained from the law itself, books from the library, and scholarly journals accessed through the internet. The conclusions drawn from this research follow a deductive method.Keywords: Legal Protection, Fraudulent Investments, Financial Services Authority